2018
DOI: 10.3389/fphar.2018.00650
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of LA7-Induced Mammary Tumor Growth by SM6Met, a Well-Characterized Cyclopia Extract

Abstract: Breast cancer (BC) is the leading cause of cancer-related deaths in women. Chemoprevention of BC by using plant extracts is gaining attention. SM6Met, a well-characterized extract of Cyclopia subternata with reported selective estrogen receptor subtype activity, has shown tumor suppressive effects in a chemically induced BC model in rats, which is known to be estrogen responsive. However, there is no information on the estrogen sensitivity of the relatively new orthotopic model of LA7 cell-induced mammary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 112 publications
1
13
0
Order By: Relevance
“…In another study, the extracts of Cyclopiasubternata reduced the volume of mammary tumor at the same rate as tamoxifen in an orthotopic rat model. Notably, in animals no side effects of tamoxifen and letrozole were reported 110 . The in vivo anticancer effects of plant derived foods against mammary carcinoma were also demonstrated by several recently published papers 14,111 .…”
Section: In Vivo Studiesmentioning
confidence: 96%
“…In another study, the extracts of Cyclopiasubternata reduced the volume of mammary tumor at the same rate as tamoxifen in an orthotopic rat model. Notably, in animals no side effects of tamoxifen and letrozole were reported 110 . The in vivo anticancer effects of plant derived foods against mammary carcinoma were also demonstrated by several recently published papers 14,111 .…”
Section: In Vivo Studiesmentioning
confidence: 96%
“…i.e., vimentin. We also considered the LA7 cells as estrogen receptor positive cells based on a previous report (23); therefore, we used this antigen in our IHC panel. As it can be realized from Figure 4, the LA7 cells transformed to Ki67 + , cytokeratin + , vimentin + , and estrogen receptor negative cells.…”
Section: La7-cscs Can Be Differentiated To Poorly Differentiated Sarcomatoid Carcinoma In Ratsmentioning
confidence: 99%
“…LA7 is a well-known rat mammary gland cancer stem cells that can be differentiated to all cell lineages of the mammary gland and is able to induce heterogeneous tumors in non-obese diabetic-SCID mice (22). Tumor induction by transplantation of LA7 cells in animal model, is recently considered as a favored method in cancer research (23). Here, we showed that 16h-SFS solution comprised of some proteins with well-known ability in reduction of the expression of stemness-related genes and in induction of cell death, upon analyzing this solution by LC-ESI-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Although they work as modulators of plant physiology, they have gained popularity in human health research, as they possess bioactive and pharmacological properties 3,4 which may have substantial benefit in the preventative medicine niche, specifically in terms of non-communicable diseases of lifestyle, 5 but also in the context of cancer. 6 From a nutritional perspective, they behave as non-nutrient bioactive compounds with antioxidant and other modulating properties in a plethora of tissues and organs. 7 The consumption of polyphenolic compounds in our diet has been recently associated with a reduction in the development of certain disorders such as cancer or cardiovascular, metabolic and neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%